A Fatal Case of Otomycosis due to Lichtheimia Spp in an Immunocompromised Patient with a Brief Review of Lichtheimia - Gautam, Tushar; Das, Anupam; Agarwal, Jyotsna; Singh, Vikramjeet; Sen, Manodeep; Kumar, Manoj; Gupta, Tejaswi (International Journal of Innovative Research in Medical Science, 2022)
The genus Lichtheimia consists of fungal species (Mucorales, Zygomycetes), which are ubiquitous soil inhabitants and represent important causative agents of mucormycoses in human and animals. Subsequent phylogenetic and physiological studies showed that Absidia-like fungi represent three separate lineages Absidia, Lentamyces, Lichtheimia. Only the last group has clinical relevance. Infection due to Lichtheimia spp is an infrequent opportunistic infection that can potentially be angioinvasive when affecting immunocompromised patient. In the present study we are discussing a case of A 68 yrs old male with type 2 diabetes, and chronic kidney disease, presented with right side otalgia with purulent discharge from right external auditory canal. This minireview throws light on fatal nature, various diagnostic modalities and treatment available for Lichtheimia.